An examination of the role of changes in country-level leisure time internet use and computer gaming on adolescent drinking in 33 European countries - Vashishtha, Rakhi (Int J Drug Policy, 2022)
INTRODUCTION: Adolescent alcohol consumption has been declining in many high-income countries since the turn of this century. Research investigating the plausible explanations for these declines has been mostly based on individual-level studies, which are largely inconclusive. Changes in leisure time internet use and computer gaming (referred to in this article as ‘computer activities’) have been hypothesised to play a role in declining adolescent alcohol consumption at a country-level. The aim of this study was to examine the association between country-level changes over time in computer activities and adolescent drinking in 33 European countries. METHODS: This is a multi-level repeated cross-national study examining the role of changes over time in country-level and individual-level computer activities on regular drinking. We utilised four waves of the European School Survey Project on Alcohol and Drugs (ESPAD) from 2003, 2007, 2011 and 2015. At an individual-level the primary exposure of interest was daily engagement in computer activities and aggregated means were used to measure country-level daily computer activities in each included country. Data were analysed using three-level hierarchical linear probability methods. RESULTS: In the fully adjusted model, for between individual effects, we found significant positive association between daily computer activities and regular drinking (β = 0.043, p-value <0.001 and 95% CI = 0.033–0.054). However, at a country-level, we did not find any association between within-country changes in daily computer activities and regular drinking (β = 0.031, p-value = 0.652 and 95% CI = -0.103–0.164. CONCLUSION: Findings from this study suggest that broad cultural shifts towards increased computer-based activities among adolescents has played a little or no role in declining adolescent drinking. Future research should be directed towards examining other high-level cultural changes which may have influenced cross-national reductions in adolescent drinking.